Deteção de manchas de óleo em imagens SAR através da combinação de características e de classificadores - Ramalho, Geraldo Luis Bezerra (2007)
Mapping ocean oil pollution by using Synthetic Aperture Radar (SAR) images is an important area of interest for environmental surveillance. One can make use of the SAR images to extract features by using different methods in order to predict if a specific region contains an oil spill or not using Artificial Neural Networks (ANN). A major problem in this approach is the number of false alarms due to misclassification. Oil spills are rare events and the number of available images containing spills is atistically small which is a limitation for the classifier performance. This work proposes the use of multiple feature sets and classifier combining methods to minimize the number of false alarms and thus, reduce the operational costs of automatic oil spill detection systems. The SAR images used in this work are not limited to a specific imaging system and different feature sets based on geometry and texture of the spills were tested. The generalization performances of classifier combination methods as boosting and bagging were compared with those resulting from single classifiers as Multilayer Perceptron (MLP) and Support Vector Machines (SVM). The experimental results suggest that oil spill characterization can be significantly improved using boosting even when few image samples are available and the feature sets have high dimensionality.